Social Determinants of Hypertension in South Nias - Herbert Wau; Ida Yustina; Fazidah Aguslina Siregar; Nurmaini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Hypertension is very rarely reported because the disease is asymptomatic and people are less aware of their health. Data on risk factors needs to be obtained as soon as possible so that prevention can be carried out as early as possible to reduce the risk of death and disability. This study aims to determine the social of hypertension in South Nias. The research was conducted with a matched case-control study. The sample amounted to 100 people, where the case numbered 50 people and the control numbered 50 people. This research was conducted in the South Nias Regency. Cases were of essential hypertension who were diagnosed by doctors at the puskesmas and controls were neighbors of cases. Analyze with Mc Nemar X2 test, and calculate OR. The results showed that most subjects aged 41-62 years old, had high school and high school education and had jobs as farmers. The bivariate analysis found risk factors for hypertension are stress (OR = 2.01 CI 95% 1,234-3,285), excessive salt consumption (OR = 1.98 CI 95% 1,269-3,119), lack of physical activity (OR = 1, 87 95% CI 1,203-2,924), and obesity (OR = 1.81 CI 95% 1,094- 3,006). The conclusion of this study is the risk factors for the occurrence of essential hypertension are stress, excessive salt consumption, lack of physical activity, and obesity. Efforts to involve all stakeholders are needed to empower POSBINDU PTM, and the participation of community leaders in helping health workers promote health both in the village environment and in the Puskesmas.